Financial Efficiency: Mexican Municipal WUO - Niebla Lizárraga, Gilberto; Somoza Ríos, Jesús Alberto; Lizárraga Bernal, Rosa del Carmen; Mares Galindo, Rosa Penelope (Industrija, 2025)
This study focuses on the financial evaluation of 32 municipal WUOs in Mexico during 2019 and 2021, applying the DEA. Thus, it seeks to answer the question: What is the financial efficiency of municipal WUOs in Mexico in 2019 and 2021, and what can be improved? The hypothesis presented in this study is that there are significant differences in the financial efficiency of municipal WUOs in Mexico. Its objective is to evaluate the financial performance of WUOs. To do this, DEA methodologies are used with the CCR and BCC models to measure technical efficiency and are applied to WUOs in terms of their evolution in average efficiency. In general, most WUOs show increasing returns to scale. Finally, WUOs must generate strategies that optimize their operational and financial efficiency, improve revenue management and adopt good practices.
Keywords: Data Envelopment Analysis, benchmarking, efficiency, Performance to Scale